Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Ok so your original equation was y=4(x-2)²-1
Therefore we need to expand the bracket to find the original equation.
To do this we need to find (x-2)²=x²-4x+4
Now we multiply this by 4 and subtract 1
4x²-16x+15 Therefore B is the answer
Therefore we need to expand the bracket to find the original equation.
To do this we need to find (x-2)²=x²-4x+4
Now we multiply this by 4 and subtract 1
4x²-16x+15 Therefore B is the answer
y = 4(x - 2)² - 1
y = 4(x² - 4x + 4) - 1
y = 4x² - 16x + 16 - 1
y = 4x² - 16x + 15
y = B(y)
y = 4(x² - 4x + 4) - 1
y = 4x² - 16x + 16 - 1
y = 4x² - 16x + 15
y = B(y)
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.